Chicken erythrocyte polynucleosomes which are soluble at physiological ionic strength and contain linker histones are highly enriched in beta-globin gene sequences. - Ridsdale, J A (1987)
Mature chicken erythrocyte polynucleosomes which are soluble at physiological ionic strength are enriched in beta-globin DNA sequences. Vitellogenin chromatin, which is not expressed in this tissue, is found in aggregation prone, salt insoluble chromatin. There is a direct correlation between the size of soluble fragments and the degree of globin gene enrichment, with the largest fragments being most highly enriched. The highly globin enriched (about 50 fold) polynucleosomes contain significantly elevated levels of acetylated histones H4, H2A.Z, and H2B, and ubiquitinated (prefix "u") histones H2A and H2B (with a significant relative increase of uH2B over uH2A). These polynucleosomes were complexed with histones H1 and H5 but at a lower level than that found in unfractionated chromatin.